How Clinician–Family Interactions Potentially Impact Clinicians' Conceptualization and Discussions Regarding Prognostic Uncertainties. Issue 1 (January 2020) - Peoples, Hayley A.; Boone, Blair; Blumenthal-Barby, Jennifer S.; Bruce, Courtenay R.
Objectives: Little is known about how clinicians perceive prognostic uncertainty. Our study objective was to identify factors that influence how prognostic uncertainty is viewed by physicians, as it relates to their communications with families. Design: Thirty semi-structured interviews with qualitative content analysis (9 surgeons, 16 intensivists, 3 nurse practitioners, and 2 "other" clinicians). We analyzed interviews using qualitative description with constant comparative techniques. Setting: Open medical, surgical, neurosurgical, and cardiovascular intensive care units (ICUs) in a 900-bed academic, tertiary Houston hospital. Interventions: None Main Results: We identified 2 main factors that influence how clinicians perceive prognostic uncertainty and their perceptions about whether and why they communicate prognostic uncertainties to families: (1) Communicating Uncertainty to "Soften the Blow"; and (2) Communicating Uncertainty in Response to Clinicians' Interpretations of Surrogate Decision Makers' Perceptions of Prognostic Uncertainty. We also identified several subthemes. Conclusions: Clinician–family interactions influence how clinicians perceive prognostic uncertainty in their communications with patients or families. We discuss ethical and clinical implications of our findings.